Enhancing Arabic Learning Using Talking Stick Model At Fatima Al-Zahraa School - Jannah, Dias Ayu Miftakhul; Abidin, Munirul (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2025)
The researcher is trying to introduce innovation in the form of the Talking Stick model in teaching Arabic language. Based on the mentioned educational issues, the objectives of this research are: To reveal the results of teaching Grade 3B students in the Arabic language lesson using the Talking Stick model at Fatima Al-Zahra Islamic Middle School Magelang. The research method used for this research is Classroom Action Research with the Kemmis and Mc Taggart models which consists of four stages: Planning, Implementation, Observation, and Reflection. The researcher conducted this research in Duran. The research subject is the students of Grade 3B at Fatima Al-Zahra Islamic Middle School Magelang with a total of 16 students. The subject of the research is student learning outcomes. The result of this research is as follows: The implementation of the Talking Stick model in the Arabic language subject (Grade 3B) has improved the students' learning outcomes as evidenced by the evidence in the first round that the students' learning outcome obtained the 50th percentile with an average of 70 out of 16 students. In the second round, the students' learning outcome obtained the 75th percentile with an average of 79.0 out of 16 students.